FRI0356 Antibodies to Perforin-Induced Citrullinated Hnrnp A1 Are Associated with Erosive Rheumatoid Arthritis. (10th June 2014) - Konig, M.F.; Giles, J.T.; Romero, V.; Andrade, F.
Abstract : Background: Perforin- and complement-induced cell lysis has recently been implicated in the generation of citrullinated autoantigens in rheumatoid arthritis (RA). By activating PADs in target cells, immune-mediated pore-forming pathways induce abnormal protein citrullination in the RA joint. Here, we demonstrate a novel approach to identify unique autoantibody reactivities to citrullinated proteins generated by the perforin pathway. Objectives: To identify novel perforin-induced autoantigens in RA, and to characterize the antibody response to citrullinated hnRNP A1 (cit-hnRNP A1) in patients with RA. Methods: 293T cells transiently transfected to express human PAD2 or PAD4 were incubated with perforin from cytotoxic granule contents (GC) to induce PAD activation. Cellular citrullination was confirmed by anti-modified citrulline (AMC) immunoblotting. Inducible autoantigens generated during perforin-mediated cytolysis were identified by immunoblotting using RA patient sera. Antigen identity was determined by 2D gel electrophoresis/mass spectrometry (MS). Recombinant hnRNP A1 was expressed in E. coli . Patients with RA (n=196) from a longitudinal cohort study (ESCAPE RA) and healthy controls (n=56) were assayed for IgG antibodies to unmodified and in vitro citrullinated hnRNP A1 by ELISA. Positivity was defined as an arbitrary unit (AU) above the 98th percentile of controls. Anti-cit-hnRNP A1 antibody specificity was determined by subtracting reactivities measured against unmodified hnRNP A1 from reactivities against cit-hnRNP A1. Results: 293T cells expressing PAD2 or PAD4 were used to study PAD-isotype specific autoantigen citrullination. A 34-kDa autoantigen inducible in both PAD2- and PAD4-transfected cells was distinctly targeted by RA patient sera (Fig. 1A; GC: perforin-treated cells, NT: untreated controls). MS identified the modified protein as cit-hnRNP A1, and citrullination by both rPAD2 and rPAD4 was confirmed using purified hnRNP A1. Antibody reactivity against cit-hnRNP A1 was detected in 70 (36%) of RA patients vs. only 1 (2%) of controls (p<0.0001: Figure 1 B; HC: healthy controls), and anti-cit-hnRNP A1 specific antibodies were confirmed in 65 (33%) of RA patients. In contrast, the low-titer reactivities against unmodified hnRNP A1 observed in patients with RA did not differ significantly from controls (7% vs. 2%; p=0.32) (Fig. 1B). Anti-cit-hnRNP A1 positivity in RA was associated with markers of erosive disease as measured using the Sharp-van der Heijde score (median 12 vs. 6 units, respectively for antibody positive vs. negative; p=0.019) and total erosion score (median 6 vs. 2 units, respectively; p=0.008) despite equivalent therapeutic intervention. Interestingly, this marker uniquely associated with elevated levels of IL-6 (58% higher in antibody positive vs. negative; p=0.01). Conclusions: These studies identify hnRNP A1 as a citrullinated autoantigen in RA generated during perforin-mediated cytotoxicity. Anti-cit-hnRNP A1 antibodies may serve as a novel biomarker associated with mechanisms of joint damage in a subset of RA. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3035